2015
DOI: 10.1093/nar/gkv1076
|View full text |Cite
|
Sign up to set email alerts
|

SigMol: repertoire of quorum sensing signaling molecules in prokaryotes

Abstract: Quorum sensing is a widespread phenomenon in prokaryotes that helps them to communicate among themselves and with eukaryotes. It is driven through quorum sensing signaling molecules (QSSMs) in a density dependent manner that assists in numerous biological functions like biofilm formation, virulence factors secretion, swarming motility, bioluminescence, etc. Despite immense implications, dedicated resources of QSSMs are lacking. Therefore, we have developed SigMol (http://bioinfo.imtech.res.in/manojk/sigmol), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 41 publications
0
82
0
Order By: Relevance
“…In previous studies, researchers found that AHL profiles were not strictly conserved at the genus or species levels (Zimmer et al, 2014; Rajput et al, 2016). Hence, some phylogenetically distant species exhibited similar AHL profiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, researchers found that AHL profiles were not strictly conserved at the genus or species levels (Zimmer et al, 2014; Rajput et al, 2016). Hence, some phylogenetically distant species exhibited similar AHL profiles.…”
Section: Discussionmentioning
confidence: 99%
“…and Aeromonas sp.) that also have AHL-degrading genes or regulators using the SigMol tool (Rajput et al, 2016). The coupling of AHL synthesis and degradation in the same bacterium has previously been noted for Agrobacterium tumefaciens , which produces and degrades 3-oxo-C8-AHL via a lactonase encoded by AttM that is activated by starvation signals and stress alarmone (p)ppGpp (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the BBCC2175 strain, also affiliated with Pseudophaeobacter, was readily identified as being able to produce C16-HSL and the only one to not produce C14:1-HSL. Previous studies revealed that the patterns of AHL production can differ between phylogenetically closely related strains (Zimmer et al, 2014;Rajput et al, 2016). Such patterns may result from the selective pressure that occurs when related organisms share the same ecological niche ).…”
Section: Discussionmentioning
confidence: 99%
“…It also enables the cell-cell communication between bacteria and other cells, with which mixed colonies can survive symbiotically or competitively (Figure 1a,c) [14]. [19]. In fungal species such as C. albicans, quorum sensing pathways are not as well understood as in prokaryotes, but the molecule farnesol has been found to be related to QS and has an inhibitory effect on bacteria such as P. aeruginosa [20].…”
Section: Biofilms -Bacterial Simplicity With Tissue-like Complexitymentioning
confidence: 99%